Perspectives in motion engaging the visual in dance and music - Stepputat, Kendra 1978-; Diettrich, Brian (Dance and performance studies, 2021)
Focusing on visual approaches to performance in global cultural contexts, Perspectives in Motion explores the work of Adrienne L. Kaeppler, a pioneering researcher who has made a number of interdisciplinary contributions over five decades to dance and performance studies. Through a diverse range of case studies from Oceania, Asia, and Europe, and interdisciplinary approaches, this edited collection offers new critical and ethnographic frameworks for understanding and experiencing practices of music and dance across the globe